Program Satisfaction of the Pioneering Graduates of the Bachelor in Secondary Education –Science in a Philippine State University - Basagre, Rey-Mark (JPAIR Multidisciplinary Research, 2024)
After the implementation of the new teacher education curricular program, the BSE major in Science program had its first batch of graduates in the academic year 2021-2022. Yet, studies on the implementation of this new curricular offering have not yet been carried out. This study utilized a descriptive survey as a method of research. This study uses a scale to gather data on the BSEd - Science program graduates’ satisfaction with the curriculum and instruction, facilities, and student support. Data were treated using mean, frequency, and rank. Interviews with college administrators, graduates, and the employers of the graduates were also conducted to gather relevant data that could help in the analysis of results. Results showed that the graduates are "satisfied" with the program’s curriculum and instruction, support to students, and facilities, with a mean of 4.4, 4.37, and 4.01, respectively. Further, the strengths and areas for improvement of the program were identified. The identified strengths of the program are an organized and flexible curriculum, learner-centered and academic freedom, relevant competencies, approachable and competent faculty, and good resources and facilities. The identified themes for the areas for improvement of the program are the improvement of the laboratory room and apparatus, hands-on laboratory activities, and others. Overall, the students are "satisfied" with implementing the new program.